2022
DOI: 10.3389/fncel.2022.809934
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Spastin Promotes the Surface Delivery and Synaptic Function of AMPA Receptors

Abstract: Synaptic plasticity is essential for cognitive functions such as learning and memory. One of the mechanisms involved in synaptic plasticity is the dynamic delivery of AMPA receptors (AMPARs) in and out of synapses. Mutations of SPAST, which encodes SPASTIN, a microtubule-severing protein, are considered the most common cause of hereditary spastic paraparesis (HSP). In some cases, patients with HSP also manifest cognitive impairment. In addition, mice with Spastin depletion exhibit working and associative memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“… 21 Further study showed that changes in excitatory synaptic currents and expression of AMPAR GluA2 on the membrane surface in rat hippocampal neurons were both affected by changes in the level of spastin phosphorylation. 43 These results seem to be consistent with ours, suggesting that phosphorylation of spastin may be closely related to its role in neuronal synaptic membrane receptors, which in turn promotes hippocampal neurite outgrowth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 21 Further study showed that changes in excitatory synaptic currents and expression of AMPAR GluA2 on the membrane surface in rat hippocampal neurons were both affected by changes in the level of spastin phosphorylation. 43 These results seem to be consistent with ours, suggesting that phosphorylation of spastin may be closely related to its role in neuronal synaptic membrane receptors, which in turn promotes hippocampal neurite outgrowth.…”
Section: Discussionsupporting
confidence: 91%
“… 41 , 42 In addition to neuronal development, there is a strong correlation between neuronal regenerative capacity and alterations of cytoskeletal microtubules and synaptic membrane receptors. 43 We found that overexpression of spastin WT significantly promoted neurite length and neurite branch formation in hippocampal neurons, whereas the promotion effect of spastin 11A was significantly reduced, indicating that spastin 11A may inhibit its function in hippocampal neurons without affecting its microtubule severing activity. The reason for this phenomenon may be that the mutation sites involved in this study are all located in two functional domains, MIT and MTBD, outside the spastin AAA functional domain.…”
Section: Discussionmentioning
confidence: 74%
“…It plays an important role in the acquisition and consolidation of learning and memory (Cui et al, 2022). At present, LTP and hippocampal synaptic plasticity have been recognized as the material basis of learning and memory (Yang & Liu, 2022;Chen et al, 2022). The formation of LTP is undergoing two stages of induction and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Spastin is fundamental during neuronal development as it mediates axon branch loss in neuromuscular synapse elimination ( Brill et al, 2016 ), and it sustains the transport of AMPA receptors and synaptic vesicles ( Sherwood et al, 2004 ; Ji et al, 2020 ; Lopes et al, 2020 ; Li et al, 2021 ; Chen et al, 2022 ). Recently, spastin was shown to contribute to MT repair ( Vemu et al, 2018 ; Kuo and Howard, 2021 ), extending the lifespan of axonal MTs by rejuvenating and protecting them against depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic plasticity is regulated by the traffic of AMPA receptors at postsynapses ( Forrest et al, 2018 ). Recently, spastin was shown to directly interact with all the four subunits of AMPA receptors, in cultured rat hippocampal neurons, with phosphorylation of spastin at Ser210 enhancing its binding and surface delivery of AMPA receptors at synapses, in a mechanism independent of MT dynamics ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%